Effective baton exchange in the 4x100 m relay race - Zarebska, E. A.; Kusy, K.; Wlodarczyk, M.; Osik, T.; Zielinski, J. (Acta Kinesiologica, 2021)
Baton exchange effectiveness and speed are essential to performance in sprint relay races, often deciding team victory. An effective baton exchange requires athletes to complete it while at full speed, both bythe incoming and the outgoing athlete. Our research aimed to determine the relationship between baton exchange time and the point in the exchange zone where the handoff is completed. The study was carried out among Polish national team sprinters (n=27), competing in the 4x100 m relays. We analyzed 168 men`s and 62 women`s baton exchanges across the annual training cycle. In a 30-meter track segment corresponding to the baton exchange zone, we measured the time the baton spent in this segment (exchange time, ET), using the Brower Timing Systems (TC-System, USA), and the exact point of the baton handoff in this zone (handoff point, HP). To show the relationship between ET and HP, we performed a linear regression analysis. We have found that the further the HPthe shorter the ET. This dependence is more evident in women (r=-0.66, r2=0.44 for 1stand 3rdexchanges, and r=-0.72, r2=0.52 for 2ndexchange; both P<0.001) than in men (r=-0.45, r2=0.20 and r=-0.68, r2=0.46; both P<0.001, respectively). The results suggest that the further the baton exchange takes place in the exchange zone (longer HP distance) the more effective the exchange (shorter ET). However, the coefficient of determination ranging (r2=0.20-0.52) indicates that HP explains at most 50% of the ET, and other factors should be taken into account. Nonetheless, the measuring technique proposed by us can provide coaches with additional data on baton exchange effectiveness and athletes' speed abilities.